Costs and benefits of multiple mating in a species with first‐male sperm precedence. Issue 4 (12th February 2020) - Rodrigues, Leonor R.; Figueiredo, Alexandre R. T.; Van Leeuwen, Thomas; Olivieri, Isabelle; Magalhães, Sara
Abstract: Different patterns of sperm precedence are expected to entail different costs and benefits of mating for each sex that translate into distinct predictions regarding mating system evolution. Still, most studies addressing these costs and benefits have focused on species with mixed paternity or last male precedence, neglecting first‐male sperm precedence. We attempted to understand whether this latter pattern of sperm precedence translates into different costs and benefits for each sex in the haplodiploid spider mite Tetranychus urticae, a species in which female multiple mating is prevalent but most offspring are sired by first males. First, we assessed the stability of the sperm precedence pattern. To do so, we measured offspring paternity after exposing females to a different number of matings and mating intervals. Next, to determine the potential costs or benefits of multiple mating for females under different contexts, we measured the fecundity and survival of females that re‐mated at different time points. To measure the potential costs of multiple mating for males, we analysed male survival in the presence of different numbers of virgin or mated females. We also tested whether males can reduce offspring production of their competitors, by reducing the production of fertilized offspring of mated females. We found no change in the pattern of sperm precedence, independently of the mating interval between matings and the number of matings. Females paid a cost of mating, as multiply‐mated females laid fewer eggs than once‐mated females. However, while males had reduced survival when exposed to an intermediate number of virgin females, they paid no additional costs of mating with mated females. Moreover, females that mated multiple times produced fewer fertilized offspring than females that mated once. Thus, males that copulated with mated females reduced the fitness of other males, potentially leading to a relative fitness benefit for themselves. Our results show that complex costs and benefits may arise in males in species with first‐male sperm precedence. How these costs and benefits affect the maintenance of selection for polyandry remains an open question. Abstract : The authors study the drivers of multiple mating in spider mites, a species with first‐male sperm precedence. Females suffer costs of multiple mating, whereas males that copulate with mated females gain a relative fitness benefit. How these costs and benefits affect selection for polyandry remains an open question. Photo credit: Miguel Cruz.